Case report: Tackling the complexities of an extremely premature newborn with intrauterine growth restriction and congenital metabolic disorders through a multidisciplinary approach - Roșca, Ioana; Preda, Andrei Gheorghe; Constantin, Andreea Teodora; Coroleucă, Ciprian; Severin, Emilia; Teleanu, Raluca Ioana; Turenschi, Alina (Frontiers in Pediatrics, 2023)
The premature birth of a newborn can present a complex challenge for healthcare providers, particularly in cases of extreme prematurity combined with intrauterine growth restriction and multiple metabolic deficiencies. In this report, we aim to shed light on the difficulties and considerations involved in the management of such a case. Case presentation and main findings: We present the case of a 28-week premature female newborn with very low birth weight (660g, percentile <10%) and intrauterine growth restriction. She was born through emergency cesarean delivery due to maternal HELLP syndrome and had a high-risk pregnancy (spontaneous twin pregnancy, with one fetus stopping development at 16 weeks and maternal hypertension). In the first hours of life, she presented persistent hypoglycemia requiring progressive glucose supplementation up to 16g/kg/day to maintain normal blood glucose levels. The baby then showed favorable progress. However, from day 24-25, hypoglycemia recurred and did not respond to glucose boluses or supplementation in both intravenous and oral feeds, leading to the suspicion of a congenital metabolic disorder. Endocrine and metabolic screenings led to suspicion of primary carnitine deficiency and a deficiency in hepatic form of CPT1 (carnitine palmitoyltransferase type I) on the second screening. Conclusion and clinical implications: The aim of this study is to raise awareness of the importance of a multidisciplinary team in managing an extreme premature case with multiple comorbidities. The study highlights rare metabolic anomalies that can be due to both organ and system immaturity and delayed enteral feeding and excessive use of antibiotics. The clinical implications of this study emphasize the need for careful monitoring and comprehensive care of premature infants to prevent and manage potential metabolic abnormalities.